126OOlaparib as maintenance treatment following first-line platinum-based chemotherapy (PBC) in patients (pts) with a germline BRCA mutation and metastatic pancreatic cancer (mPC): Phase III POLO trial. (24th November 2019) - Oh, D-Y; Golan, T; Hammel, P; Reni, M; Van Cutsem, E; Macarulla, T; Hall, M J; Park, J Oh; Hochhauser, D; Arnold, D; Reinacher-Schick, A; Tortora, G; et al.
Abstract: Background: The unmet need for effective and tolerable mPC treatments is high. PC pts with a germline BRCA1 and/or BRCA2 mutation (gBRCAm) have shown response to the PARP inhibitor olaparib (O; Kaufman 2015). POLO (NCT02184195), the first Phase III trial to evaluate the efficacy of maintenance PARP inhibitor treatment in PC, demonstrated a statistically significant and clinically meaningful improvement in progression-free survival (PFS) from maintenance O vs placebo (P) for pts with a gBRCAm and mPC whose disease had not progressed during PBC (median 7.4 vs 3.8 months; hazard ratio [HR] 0.53; 95% CI 0.35–0.82; P = 0.004). At 2 years, 22.1% of pts on O vs 9.6% of pts on P were progression free. At an interim overall survival analysis (46% maturity), the HR was 0.91 (95% CI 0.56–1.46; P = 0.68). Safety was consistent with the known profile for O (Golan 2019). Methods: POLO is a randomized, double-blind, placebo-controlled trial of pts with a gBRCAm and pancreatic adenocarcinoma who had received ≥16 weeks of first-line PBC for mPC without progression. There was no limit to duration of chemotherapy. Pts were randomized 3:2 to maintenance O tablets (300 mg bid) or P. Treatment began 4–8 weeks after the last PBC dose, continuing until investigator-assessed progression or unacceptable toxicity. The primary endpoint, PFS, and objective response were assessed by blinded independent central review (modified RECIST 1.1). Results: Objective response rate among pts with measurable disease at baseline was 23.1% (18/78) in the O and 11.5% (6/52) in the P arm (odds ratio 2.30; 95% CI 0.89–6.76; P = 0.103). Conclusions: Pts with a gBRCAm and mPC whose disease had not progressed on PBC derived a statistically significant and clinically meaningful PFS benefit from maintenance O. O-arm pts were more likely to maintain disease control or achieve a response than P-arm pts, and responses were durable, lasting a median of more than 2 years. Clinical trial identification: NCT02184195. Editorial acknowledgement: Medical writing assistance was provided by Elin Pyke, MChem, from Mudskipper Business Ltd, funded by AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Legal entity responsible for the study: AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Funding: AstraZeneca and Merck Sharp & Dohme Corp, a subsidiary of Merck & Co, Inc, Kenilworth, NJ, USA. Disclosure: D-Y. Oh: Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: Novartis; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Bayer; Advisory / Consultancy: Taiho; Advisory / Consultancy: ASLAN; Advisory / Consultancy: Halozyme. T. Golan: Honoraria (self), Research grant / Funding (self), International coordinating investigator service fee: AstraZeneca; Research grant / Funding (self): MSD Merck; Advisory / Consultancy, Speaker Bureau / Expert testimony: AbbVie. P. Hammel: Research grant / Funding (self): Celgene; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self), Non-remunerated activity/ies: Erythec; Research grant / Funding (self): Halozyme. M. Reni: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Non-remunerated activity/ies, Steering committee member: Celgene; Advisory / Consultancy: Baxalta; Advisory / Consultancy: Shire; Advisory / Consultancy: Eli-Lilly; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Novocure; Advisory / Consultancy: Novartis; Advisory / Consultancy, Steering Committee member: AstraZeneca; Advisory / Consultancy, Steering Committee member: Boston Pharma. E. Van Cutsem: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (self): Bayer; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (self): Celgene; Advisory / Consultancy, Research grant / Funding (self): Lilly; Advisory / Consultancy, Research grant / Funding (self): Merck Sharp & Dohme; Advisory / Consultancy, Research grant / Funding (self): Merck KGaA; Advisory / Consultancy, Research grant / Funding (self): Novartis; Advisory / Consultancy, Research grant / Funding (self): Roche; Advisory / Consultancy, Research grant / Funding (self): Servier; Research grant / Funding (self): Amgen; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): Ipsen. T. Macarulla: Honoraria (self): Genzyme; Honoraria (self), Research grant / Funding (institution): Roche; Honoraria (self), Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Sanofi/Aventis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Shire; Honoraria (self): Tesaro; Advisory / Consultancy: Baxalta; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Celgene; Advisory / Consultancy, Travel / Accommodation / Expenses: H3B; Advisory / Consultancy: QED; Research grant / Funding (institution): Agios; Research grant / Funding (institution): Aslan; Research grant / Funding (institution): AstraZeneca; Travel / Accommodation / Expenses: Bayer, Merck; Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Hallozyme; Research grant / Funding (institution): Immunomedics; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Merimarack; Research grant / Funding (institution): Millennium; Research grant / Funding (institution): Novartis, Novocure, Pfizer, Pharmaclynics. M.J. Hall: Research grant / Funding (institution), Travel / Accommodation / Expenses, Non-remunerated activity/ies: AstraZeneca; Research grant / Funding (institution): Merck; Travel / Accommodation / Expenses: Caris Lifesciences; Non-remunerated activity/ies: Myriad; Non-remunerated activity/ies: Ambry; Non-remunerated activity/ies: Invitae; Non-remunerated activity/ies: Foundation Medicine; Non-remunerated activity/ies: Caris; Non-remunerated activity/ies: Merck. J. Oh Park: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Celgene; Honoraria (self), Advisory / Consultancy: Sanofi; Honoraria (self), Advisory / Consultancy: Shire; Advisory / Consultancy: Merck; Advisory / Consultancy: Sereno. D. Arnold: Honoraria (self): AstraZeneca; Honoraria (self), Non-remunerated activity/ies: Bayer; Honoraria (self), Non-remunerated activity/ies: BMS; Honoraria (self): Biocompatibles; Honoraria (self): Eli Lilly; Honoraria (self), Non-remunerated activity/ies: MSD; Honoraria (self), Non-remunerated activity/ies: Servier; Honoraria (self), Non-remunerated activity/ies: Sanofi; Honoraria (self), Non-remunerated activity/ies: Roche; Honoraria (self): Terumo; Honoraria (self), Non-remunerated activity/ies: Sirtex. A. Reinacher-Schick: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Amgen; Honoraria (self), Advisory / Consultancy: Baxalta; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Celgene; Honoraria (self), Research grant / Funding (institution): Ipsen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Lilly; Honoraria (self), Advisory / Consultancy: Merck-Serono; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self), Advisory / Consultancy: Sanofi-Aventis; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Servier; Honoraria (self): Shire; Research grant / Funding (institution): Astra. G. Tortora: Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck; Honoraria (self), Advisory / Consultancy: Incyte; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis. H. Algül: Honoraria (self): Celgene; Honoraria (self), Travel / Accommodation / Expenses: Servier; Research grant / Funding (institution): Chugai. E.M. O'Reilly: Advisory / Consultancy: 3DMedcare, Agios, Alignmed, Amgen, Antengene, Aptus, Aslan, Astellas, AstraZeneca; Advisory / Consultancy: Bayer, Beigene, Bioline, BMS, Boston Scientific, Bridgebio, ; Advisory / Consultancy: Carsgen, Celgene, Casi, Cipla, CytomX; Advisory / Consultancy: Daiichi, Debio, Delcath; Advisory / Consultancy: Eisai, Exelixis, Genoscience; Advisory / Consultancy: Halozyme, Hengrui; Advisory / Consultancy: Incyte, Inovio, Ipsen; Advisory / Consultancy: Jazz, Janssen; Advisory / Consultancy: Kyowa Kirin; Advisory / Consultancy: LAM, Lilly, Loxo; Advisory / Consultancy: Merck, Mina; Advisory / Consultancy: Novella; Advisory / Consultancy: Onxeo; Advisory / Consultancy: PCI Biotech, Pfizer, Pieris; Advisory / Consultancy: QED, Redhill; Advisory / Consultancy: Sanofi, Servier, Silenseed, Sillajen, Sobi; Advisory / Consultancy: Targovax, Tekmira, Twoxar; Advisory / Consultancy: Vicus, Yakult, Yiviva; Research grant / Funding (institution): ActaBiologica, Agios, Array, AstraZeneca, Bayer, Beigene, BMS, Casai, Celgene, Exelisis, Genentech, Halozyme, Incyte, Lilly, Mabvax, Novartis, OncoQuest, Polaris Puma, QED, Roche. D. McGuinness: Full / Part-time employment: AstraZeneca. K.Y. Cui: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca; Research grant / Funding (institution): Merck and Co. Inc. K. Schlienger: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. G.Y. Locker: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. H.L. Kindler: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck; Advisory / Consultancy: Aldeyra Therapeutics; Advisory / Consultancy: Astellas; Advisory / Consultancy, Travel / Accommodation / Expenses: Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): BMS; Advisory / Consultancy: Erytech; Advisory / Consultancy: Five Prime Therapeutics; Advisory / Consultancy: Ipsen Pharmaceuticals; Advisory / Consultancy: Kyowa; Advisory / Consultancy, Travel / Accommodation / Expenses: Paredox Therapeutics; Research grant / Funding (institution): Aduro; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Deciphera; Research grant / Funding (institution): Glaxo Smith Kline; Research grant / Funding (institution): MedImmune; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Polaris; Research grant / Funding (institution): Verastem. All other authors have declared no conflicts of interest.